Psychometric Properties of the Persian Version of the 6-item De Jong Gierveld Loneliness Scale in Iranian Community-dwelling Older Persons - Reza Hosseinabadi; Mahshid Foroughan; Gholam Reza Ghaed Amini Harouni; Razieh Zeidali Beiranvand; Yadollah Pournia (University of Social Welfare & Rehabilitation Sciences, 2020)
Objectives: Loneliness is a significant concern among the elderly and requires measurement and intervention. This study was conducted to translate and make a psychometric evaluation of the 6-item de Jong Gierveld loneliness scale in Iranian older people. Methods & Materials: This is a descriptive study carried out in 2018. After receiving permission from the tool designer, the original version of the 6-item de Jong Gierveld loneliness scale was translated into Persian by the translation and translation-back method. Then its face and content validities were determined. The final Persian version was completed by 224 eligible elderly residents in Khorramabad City, Iran. The data were analyzed using Confirmatory Factor Analysis (CFA), the Pearson correlation coefficient, the Intra-class Correlation Coefficient (ICC), and the Cronbach alpha. The SPSS and AMOS were used, and the significance was determined at the level of P≤ 0.05. Results: The Persian version of the 6-item de Jong Gierveld Loneliness Scale had an acceptable content validity (CVI=0.874).  Confirmative factor analysis indicated the extraction of two factors: emotional loneliness and social loneliness (CMIN/DF=1.48, GFI=0.983, IFI=0.983, RMSEA=0.004). The overall loneliness score showed a significant correlation with the hospital anxiety and depression scale. The reliability of the scale was accepted by the intra-class correlation coefficient and the Cronbach alpha coefficient. Conclusion: The Persian version of the 6-item de Jong Gierveld loneliness scale is a reliable and valid measure of loneliness in Iranian elders.